(untitled) (Conference Zone, 2022)
Word etiquette French by origin (etiquette); initially it denoted a commodity tag, a label, and then they began to call it the court ceremonial. It is in this meaning, especially after the adoption of the French ceremonial at the Vienna court, that the word etiquette gained distribution in German, Polish, Russian and other languages.1 Along with this word, the word is used to denote the totality of the adopted rules that determine the order of any activity, regulation and the phrase diplomatic protocol.